Does exchange rate variability matter for welfare? A quantitative investigation of stabilization policies - Paul Bergin; Hyung-Cheol Shin; Ivan Tchakarov (University of California, Department of Economics, 2005)
This paper evaluates quantitatively the potential welfare gains from monetary policy and fixed exchange rate rules in a two-country sticky-price model. The first finding is that the gains from stabilization tend to be small in the types of economic environments emphasized in recent theoretical literature. The analysis goes on to identify two types of economies in which the welfare implications of risk are larger: where agents exhibit habits, and where international asset markets exhibit asymmetry in the form of "original sin." In the habits case, monetary policy aimed solely at inflation stabilization is optimal. But in the original sin case there are potentially large welfare gains from also eliminating exchange rate volatility.
Keywords: F41; 330; Wechselkursrisiko; Wohlfahrtseffekt; Zwei-Länder-Modell; Finanzmarkt; Theorie